Knowledge Management Factors and Their Impact on Competitive Priorities - Sarah Ali Saeed, Saadoon Muhsin Salman, Salma Hatyta Raheemah, (Opción, 2019)
The purpose of this research is to diagnose and limit knowledge factors that have a significant impact on the organization's competitive priorities via comparative qualitative research method. The results of the study showed that knowledge management factors have a direct and significant impact on competitive priorities, this directly affects the organization. In conclusion, the survival and profitability of the organization depends on the extent of its competitive products and services, regardless of the industry or economic branch to which it belongs.